Safety of contrast media in cerebral angiography: iopamidol vs. methylglucamine iothalamate. - Bird, C R; Drayer, B P; Velaj, R; Triolo, P J; Allen, S; Bates, M; Yeates, A E; Heinz, E R; Osborne, D R (American Journal of Neuroradiology, 1984)
A randomized double-blind study was performed in 27 patients to compare the clinical safety, incidence of pain and warmth, and film quality produced by iopamidol and Conray-60 in selective cerebral angiography. No complications or adverse reactions occurred in either group. Iopamidol was significantly less painful than was methylglucamine iothalamate for common carotid artery injections and caused significantly less heat in both common carotid and internal carotid artery injections. Film quality and diagnostic accuracy were excellent in both groups. These results, when viewed in conjunction with laboratory data demonstrating the decreased neurotoxicity of nonionic contrast agents, suggest that iopamidol is an important advance in the development of angiographic contrast media.